Special Features of Creativity at the Teenage Period - Shumakova N.B (Moscow State University of Psychology and Education, 2018)
The article is devoted to a study of the aged differences in creativity of junior adolescents. The paper presents the results of an empirical study of the dynamics of verbal and nonverbal (figural) creativity of the school children of the 4th, 5th and 7th classes. The hypothesis tested was that the creativity of the adolescents characterized by special features which are manifested in its qualitative uniqueness, but not in the quantity indicators of fluency, flexibility and originality. Within the framework study is proposed the original test of the study of verbal and figural creativity. In the study took part 147 school boys and girls at the age from 10 to 14 years old. It was shown that the dynamics of the indices of verbal and figural creativity at the teenage period has opposite direction: an increase in verbal creativity is accompanied by reduction in the figural (at the level of tendency). The special features of adolescent's creativity are revealed in the qualitative uniqueness both of the verbal and nonverbal manifestations of the creativity.